Principal's Leadership in Improving Teacher and Staff Performance - Marsinah, Marsinah (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2024)
This study discusses how the leadership role of school principals in improving teacher performance. The Principal's Role as a Learning Leader. Learning leadership is an action that leads to the creation of a school climate that is able to encourage optimal learning processes. The actions taken by (the principal) to develop a productive and satisfying work environment for teachers are ultimately able to create improved student learning conditions. The research used is a qualitative approach with interview and observation methods as a way to collect data. Learning leadership is the action of the principal / madrasah in; influencing, moving, directing, developing, empowering teachers. So as to create conducive school conditions as a place for optimal learning process.